2020
DOI: 10.1080/13504509.2020.1839808
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of carbon emissions in a European emerging country: evidence from ARDL cointegration and Granger causality analysis

Abstract: Hungary is one of the European Union's most dynamically developing countries in Central-Eastern Europe with a high income and increasing level of environmental degradation. The present study explores the dynamic relationship between economic growth, electricity consumption, carbon emissions and urbanization in Hungary for period 1974-2014 based on annual data. Using autoregressive distributed lag model, we found long run relationship among the variables in the presence of structural breaks and Toda-Yamamoto pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…Pollutants released as a result of these activities affect the Environment, as [ 80 ] stated. While tourism spending in rural areas benefits the economy, the associated activities have environmental consequences for the host country due to their role in generating greenhouse gas emissions and air pollution [ 49 ]. In response to the above claims, we included the various tourism-related sectors in our environmental impact analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pollutants released as a result of these activities affect the Environment, as [ 80 ] stated. While tourism spending in rural areas benefits the economy, the associated activities have environmental consequences for the host country due to their role in generating greenhouse gas emissions and air pollution [ 49 ]. In response to the above claims, we included the various tourism-related sectors in our environmental impact analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Ref. [ 49 ] documented that more than 14,000 research works on the tourism industry-environment linkages demonstrate no environmental impacts at the sectoral tourism industry level. However, [ 50 ] found that cafeterias and lodges emit CO 2 and degrade air quality.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For instance, decision of where to build garbage treatment plants may cause social disputes or conflicts among communities (O’Neil, 2020). What is more, as the total resources or budgets of a city are relatively limited, more devotion to environmental urbanization means less devotion into social urbanization, which hinders the growth of social urbanization; in other words, environmental urbanization to some degree is at the cost of social urbanization (Nemeth-Durko, 2020). In conclusion, the dimensions of social urbanization and environmental urbanization are mutually and complicatedly intertwined.…”
Section: Introductionmentioning
confidence: 99%